Politics of art : the creation society and the practice of theoretical struggle in Revolutionary China - Yin, Zhiguang (Ideas, history, and modern China, 2014)
In Politics of Art Zhiguang Yin investigates members of the Creation Society and their social network while in Japan. The study contextualises the Chinese left-wing intellectual movements and their political engagements in relation with the early 20th century international political events and trends in both East Asia and Europe. The Creation Society was largely viewed as a subject of literary studies. This research, however, evaluates these intellectuals in the context of Chinese revolution and elaborates their theoretical contribution to the Chinese Communist Party’s practice of “theoretical struggle” as a main driving force of ideological construction. As this study tries to demonstrate, theoretical struggle drives the ideological politics forward while maintaining its political vigour.
Keywords: Intellectuals : Political activity : Japan; Chinese literature : Societies, etc; Chinese : Japan : Societies, etc; China : Intellectual life : 20th century